Expression of a Malassezia Codon Optimized mCherry Fluorescent Protein in a Bicistronic Vector - Goh, Joleen P. Z.; Ianiri, Giuseppe; Heitman, Joseph; Dawson, Thomas L. (Frontiers in Cellular and Infection Microbiology, 2020)
The use of fluorescent proteins allows a multitude of approaches from live imaging and fixed cells to labelling of whole organisms, making it a foundation of diverse experiments. Tagging a protein of interest or specific cell type allows visualization and studies of cell localization, cellular dynamics, physiology, and structural characteristics. In specific instances fluorescent fusion proteins may not be properly functional as a result of structural changes that hinder protein function, or when overexpressed may be cytotoxic and disrupt normal biological processes. In our study, we describe application of a bicistronic vector incorporating a Picornavirus 2A peptide sequence between a NAT antibiotic selection marker and mCherry. This allows expression of multiple genes from a single open reading frame and production of discrete protein products through a cleavage event within the 2A peptide. We demonstrate integration of this bicistronic vector into a model Malassezia species, the haploid strain M. furfur CBS 14141, with both active selection, high fluorescence, and proven proteolytic cleavage.Potential applications of this technology can include protein functional studies, Malassezia cellular localization, and co-expression of genes required for targeted mutagenesis.